Improvement of antagonism and fungicides tolerance in Trichoderma harzianum and T.viride local isolates by Ultra-Violet irradiation - Abdullah Abdul Kareem Hassan (Tikrit Journal of Pure Science)
Among 22 Iraqi Trichoderma harzianum  and T.viride isolates, T3,T5,D5,S1 and S6 related to T. harzianum  showed a higher antagonistic activity against the plant pathogenic fungi  Fusarium oxysporum and Rhizoctonia solani. These isolates were selected for improvement their biocontrol activity by usi